Juristische Zeitgeschichte : Das Ansehen des Staates im t©ơrkischen und deutschen Strafrecht - Dagasan, Zekai (Juristische Zeitgeschichte / Abteilung 5., 2015)
Thisstudy investigates the development of criminal provisions for protecting the reputation of the state in Turkey and Germany. It presents the current status of legislation and case law, comparing the two legal systems with respect to legal dogma, statistics, and criminal policy. The study examines problem areas in penal and constitutional law with regard to criminal offences.